Characteristics of dyadic care types among patients living with multiple chronic conditions and their informal caregivers. (6th September 2021) - De Maria, Maddalena; Ferro, Federico; Ausili, Davide; Buck, Harleah G.; Vellone, Ercole; Matarese, Maria
Abstract: Aims: To examine the distribution of dyadic care types in multiple chronic conditions, compare self‐care and caregiver contributions to patients' self‐care in each care type and identify the patient and caregiver characteristics associated with each care type. Design: Secondary analysis of a multicentre, cross‐sectional study. Methods: Patient‐caregiver dyads were enrolled from outpatient clinics and community settings. The Dyadic Symptom Management Type Scale was used to categorize dyads by type. Self‐care, self‐efficacy, comorbidities and cognitive impairment were measured in patients, whereas caregiver contributions to patient self‐care, self‐efficacy, caregiver burden and hours of caregiving were measured in caregivers. Sociodemographic characteristics perceived social support and mutuality were measured in both patients and caregivers. Univariate and multivariate analyses were performed. Results: A sample of 541 patient‐caregiver dyads was examined. The most frequent dyadic care type was the collaborative‐oriented (63%). In the patient‐oriented type, patients scored higher on self‐care compared with caregivers; in the caregiver‐oriented and collaborative types, caregivers scored higher than patients supporting the typology. The patient‐oriented type was associated with younger, healthier male patients with better cognitive status, who scored higher for mutuality and whose caregivers scored lower for burden. The caregiver‐oriented type was associated with older, less educated patients, with caregivers experiencing higher burden and unemployment. The collaborative type was associated with sicker patients, with the caregiver more probably to be female and employed, with higher perceived social support, mutuality and burden. The incongruent dyadic care type was associated with lower caregiver mutuality. Impact: In the context of multiple chronic conditions, clinicians should consider targeting any educational interventions aimed at improving patient self‐care and caregiver contributions to self‐care by dyadic care types.